RESILIENSI MATEMATIS MAHASISWA TADRIS MATEMATIKA PADA MATA KULIAH GEOMETRI ANALITIK - Ressy Rustanuarsi (LPPM Universitas Bina Bangsa, 2023)
One of the affective aspects believed to support students' success in mathematics is mathematical resilience. This study aims to describe the mathematical resilience of Tadris Matematika students in the analytical geometry course. This study used a descriptive method with a quantitative approach. This study involved all the third-semester students who enrolled in the analytical geometry course in Tadris Matematika IAIN Pontianak, totaling 28 students. Data collection in this study used a mathematical resilience questionnaire consisting of 9 indicators. Data analysis in this study used descriptive statistics. The results showed that: 1) out of 28 students, there are 4 students with high mathematical resilience (14,29%), 19 students with intermediate mathematical resilience (67,85%), and 5 students with low mathematical resilience (17,86%); and 2) based on the achievement of the obtained indicators, improvement is needed in students' attitudes towards recognizing their limitations and understanding the necessary aspects to learn and master analytical geometry